Shape-Memory Metallopolymers Based on Two Orthogonal Metal–Ligand Interactions - Meurer, Josefine; Hniopek, Julian; Baetz, Thomas; Zechel, Stefan; Enke, Marcel; Vitz, Juergen; Schmitt, Michael; Popp, Jürgen; Hager, Martin D.; Schubert, Ulrich S. (Advanced Materials, 2021)
A new shape-memory polymer is presented, in which both the stable phase as well as the switching unit consist of two different metal complexes. Suitable metal ions, which simultaneously form labile complexes with histidine and stable ones with terpyridine ligands, are identified via isothermal titration calorimetry (ITC) measurements. Different copolymers are synthesized, which contain butyl methacrylate as the main monomer and the metal-binding ligands in the side chains. Zn(TFMS)2 and NiCl2 are utilized for the dual crosslinking, resulting in the formation of metallopolymer networks. The switching temperature can simply be tuned by changing the composition as well as by the choice of the metal ion. Strain fixity rates (about 99%) and very high strain recovery rates (up to 95%) are achieved and the mechanism is revealed using different techniques such as Raman spectroscopy.
CRIS-Team Scopus Importer:2023-04-20
Keywords: metallopolymers; shape-memory polymers; smart materials; supramolecular polymers